Enhanced quality of nutrition services during antenatal care through interventions to improve maternal nutrition in Bangladesh, Burkina Faso, Ethiopia, and India - Nguyen, Phuong Hong; Mai, Lan T.; Kachwaha, Shivani; Sanghvi, Tina; Mahmud, Zeba; Zafimanjaka, Maurice G.; Walissa, Tamirat; Ghosh, Sebanti; Kim, Sunny S. (Elsevier, 2024)
Objectives: Quality antenatal care (ANC) services are critical for maternal health and nutrition. Information on quality of nutrition interventions during ANC is scarce in low-and middle-income countries. Our study examined the effects of intensified maternal nutrition interventions during ANC on service readiness, provision of care, and client’s experience of care in Bangladesh (BD), Burkina Faso (BF), Ethiopia (ET), and India (IN). We also examined inter-relationships between the dimensions of ANC quality.